Analisis Statistik Nonparametrik pada Perbedaan Tingkat Kepuasan Pelanggan terhadap Layanan Bank Syariah Indonesia dalam Perspektif Demografis - Adil Alfarizi Nst; Imsar Imsar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study investigates the differences in customer satisfaction levels toward the services of Bank Syariah Indonesia by employing a nonparametric statistical approach. Customer satisfaction is a critical benchmark in Islamic banking, as it not only reflects the quality of services but also the extent to which sharia compliance is embedded in financial practices. Given that satisfaction data are generally ordinal and may not fulfill the assumptions of normal distribution, nonparametric methods such as the Kruskal-Wallis and Mann-Whitney tests were selected as the primary analytical tools. This research adopts a qualitative library-based method by reviewing relevant literature, scientific articles, and previous empirical studies to construct a comprehensive understanding of customer satisfaction measurement within Islamic banking. The findings highlight that variations in satisfaction are influenced by multiple factors, including service speed, staff friendliness, accessibility of digital platforms, and clarity of sharia principles applied in daily operations. Results further suggest that demographic characteristics and service usage frequency significantly shape satisfaction differences across customer groups. Theoretically, this study enriches the body of knowledge on the application of nonparametric statistics in Islamic banking research, while practically, it provides actionable insights for Bank Syariah Indonesia in formulating adaptive service strategies. These contributions are expected to assist the bank in strengthening customer loyalty, enhancing competitiveness, and sustaining growth in the dynamic modern banking industry. Theoretically, this study enriches the body of knowledge on the application of nonparametric statistics in Islamic banking research, while practically, it provides actionable insights for Bank Syariah Indonesia in formulating adaptive service strategies. These contributions are expected to assist the bank in strengthening customer loyalty, enhancing competitiveness, and sustaining growth in the dynamic modern banking industry.